The role of endogenous antibacterial peptides in pneumonia occurrence among children of young age - G.O. Lezhenko; A.E. Abaturov; O.E. Pashkova; H.V. Kraynya (Zaslavsky O.Yu., 2017)
The comprehensive examination included 204 children with community-acquired pneumonia aged 2 months to 3 years. It was found that in young children with community-acquired pneumonia, the main etiologic factor is bacteria Streptococcus pneumoniae (36.8 %). The content of endogenous antimicrobial peptides was identified in the serum of 20 young children with pneumonia and in 17 children in the control group. It is proved that the development of pneumonia in young children occurs on the background of the reduction in the blood serum levels of β1-defensin and cathelicidin LL-37. The lowest values of LL-37 were identified in children with pneumonia caused by Streptococcus pneumoniae. The analysis of the content of vitamin D metabolites in the serum showed that in children with pneumonia, concentration of 25-hydroxyvitamin D was 1.4 times lower compared with healthy children (р < 0.05). Established deficiency of vitamin D metabolites in young children with community-acquired pneumonia serves as an important pathogenetic factor for cathelicidin LL-37 deficiency in the blood serum, which was confirmed by 3.7-times decrease in the percentage of LL-37 compared with vitamin D metabolites in this cohort of patients.